Mineral parageneses of basic to intermediate metamorphic rocks in the Yamato Mountains, East Antarctica - Asami, Masao; Shiraishi, Kazuyuki (1983)
P(論文) Two groups of metamorphic rocks are found in association with syenitic and granitic rocks in the Yamato Mountains; Group I includes two-pyroxene-bearing gneiss and amphibolite, whereas Group II consists of granitic gneiss and associated rocks accompanied by no orthopyroxene. Mineral parageneses of basic to intermediate metamorphic rocks of the two groups were examined in the simplified system (Al)_2O_3-FeO-MgO-CaO-(Na)_2O. Microprobe analyses reveal that hornblende of Group I is of pargasitic composition but hornblende of Group II has broad compositions ranging from tremolitic to pargasitic ones. Mineral parageneses of the two groups are incompatible with each other in such ways that the hornblende-plagioclase assemblage of Group I has higher (Na/Ca)^<M4>_<Hb>/(Na/Ca)_ values than that of Group II, and that the clinopyroxene-hornblende tie lines of Group II are mostly included in the two-pyroxene-hornblende triangles of Group I in the (Al)_2O_3-FeO-MgO-CaO tetrahedron. The hornblende-bearing assemblages of Group II are considered to be of the amphibolite facies but not the granulite facies. Although no direct contact between the granulite-facies and amphibolite-facies metamorphic rocks has been found in the Yamato Mountains, the geological and petrological relations of the syenitic rocks to the metamorphic rocks suggest that the granulite-facies rocks and the syenitic rocks form a geological unit which is in tectonic contact with the other geological unit composed of the amphibolite-facies rocks. departmental bulletin paper